Women, Ethics of Care, Domestic Role And Islamic Teachings (Classical Fiqih) and Local Culture - Saiddaeni Saiddaeni; Achfan Aziz Zulfandika (Pusat Studi Gender Universitas Jember, 2023)
Islam and Feminism, both are perceived as incompatible. However, this view is sadly only generated by the Western when they see Islam in the Middle Eastern. It even misleads when the Western has been only looking for particular countries which practice conservative and textual Islam. In reality, Islam put women in a respectful position, and though Islam has different points of view from some points in feminism, it does not mean they are against each other. Here in this paper, I tried to analyse a comparative study between how our Indonesian culture and how Islamic teachings perceive the role of women in their domestic reality and how women can participate in every day life. Interestingly, the role of women fits into the role of women from the perspective of Ethics of Care. In Ethics of care, it is believed that women’s power on taking care of other people is the key to their strength and somehow when we learn Islam deeper, we will find it is connected and this paper proves it. Here we make structure our paper starting with an introduction, later we talk about classical Fiqih. The reason why we choose classical Fiqih is that we want to understand the root of Islamic teachings on the blatant reality so we can understand how Islam sees a woman in reality. Later, we will discuss a comparison between our culture in general and Islamic Teaching so we will have insight into which one is part of our culture and which one is purely Islamic teachings. From our findings, we found that our culture and Islamic teaching have relatively similar points of view on women’s role in domestic reality. However, the conservative approach is coming from misunderstanding and, people's attitudes to mixing Islamic teachings with their Khawarij culture which is not a real Islam yet because people from outside of the Islamic world do not understand, they tend to think it is a real Islam which is giving Islam a bad reputation.